Status epilepticus complicating a hemorrhagic and ischemic stroke due to primary cerebral angiitis: A case report - Mehdi Oudrhiri Safiani; Abdallah Bennasser; Ahmed El Mostarchid; Mohamed Jiddane; Firdaous Touarsa (Radiology Case Reports)
Primary angiitis of the central nervous system (CNS), also known as “isolated” or “idiopathic” angiitis, is a rare condition characterized by inflammation of cerebral vessels in the absence of an identifiable cause. This contrasts with secondary angiitis, which is associated with systemic diseases, infections, or toxic exposures. The clinical presentation of primary angiitis is highly variable and, in severe cases, may include ischemic or hemorrhagic strokes or refractory status epilepticus (SE).We present a unique case of a 45-year-old female patient with a history of primary CNS angiitis, admitted to the intensive care unit for refractory SE secondary to concurrent ischemic and hemorrhagic strokes. This rare combination of SE, stroke, and CNS angiitis is exceptionally uncommon in the literature and underscores the diagnostic and therapeutic challenges of this condition. This case highlights potential pathophysiological mechanisms, diagnostic difficulties, and management strategies in a highly complex clinical scenario.